Current status of the surgery-first approach (part I): concepts and orthodontic protocols - Choi, Dong-Soon (Maxillofac Plast Reconstr Surg, 2019)
The “surgery-first” approach, defined as a team approach between surgeons and orthodontists for orthognathic surgery without preoperative orthodontic treatment, is aimed at dental decompensation. A brief historical background and indications for the surgery-first approach are reviewed. Considering the complicated mechanism of postoperative orthodontic treatment, the proper selection of patients is a vital component of successful surgery-first approach.